Pengaruh Perceived Quality dan Value Dimediasi Brand Trust Terhadap Brand Loyalty Tupperware di Jakarta - Gino Ernesto Un; Carunia Mulya Firdausy (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to determine the influence of perceived quality and perceived value on Tupperware brand loyalty in Jakarta with brand trust as a mediating variable. The research sample consists of 149 respondents who have purchased Tupperware products at least twice and reside in Jakarta. The sample selection used a non-probability sampling method with purposive sampling, by distributing questionnaires and analyzing the data using SEM-PLS. The results of this study show that perceived quality and perceived value have a positive and significant influence on Tupperware brand loyalty in Jakarta, both directly and through the mediation of brand trust. Furthermore, brand trust has a positive and significant effect on brand loyalty.